2022
DOI: 10.3390/ma15217502
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Core–Shell Rubber Nanoparticles on the Mechanical Properties of Epoxy and Epoxy-Based CFRP

Abstract: The aim of the research was to estimate the effect of core–shell rubber (CSR) nanoparticles on the tensile properties, fracture toughness, and glass transition temperature of the epoxy and epoxy-based carbon fiber reinforced polymer (CFRP). Three additives containing CSR nanoparticles were used for the research resulting in a filler fraction of 2–6 wt.% in the epoxy resin. It was experimentally confirmed that the effect of the CSR nanoparticles on the tensile properties of the epoxy resin was notable, leading … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Studying the mode-I interlaminar fracture toughness of composites usually determines two values: the initiation and propagation fracture toughness. [16][17][18][19][20] The initial fracture toughness was 427.6 J/m 2 for CF/EP composite, while if GF/EP composite is used, the initial fracture increases to 693.6 J/m 2 . When replacing CF/EP composite by GF/EP, the propagation fracture toughness was increased from 530.9 to 735.1 J/m 2 .…”
Section: Mode-i Interlaminar Fracture Toughness Testmentioning
confidence: 99%
“…Studying the mode-I interlaminar fracture toughness of composites usually determines two values: the initiation and propagation fracture toughness. [16][17][18][19][20] The initial fracture toughness was 427.6 J/m 2 for CF/EP composite, while if GF/EP composite is used, the initial fracture increases to 693.6 J/m 2 . When replacing CF/EP composite by GF/EP, the propagation fracture toughness was increased from 530.9 to 735.1 J/m 2 .…”
Section: Mode-i Interlaminar Fracture Toughness Testmentioning
confidence: 99%
“…The tensile and flexural properties of the epoxy blends were evaluated and was found that just a low amount of GO (less than 0.6 wt.%) was sufficient to improve the performance. Aniskevich and team [28] incorporate three additives containing core-shell rubber (CSR) nanoparticles into the epoxy resin. The tensile properties, fracture toughness and glass transition temperature of the epoxy and epoxy-based CFRP were then investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Glaskova-Kuzmina et al [ 12 ] reported on the effect of core–shell rubber nanoparticles on the tensile properties, fracture toughness, and glass transition temperature of the epoxy and epoxy-based carbon fiber reinforced polymer. The Hansen model was applied to describe the elastic modulus of the epoxy possessing a certain fraction of the core–shell rubber nanoparticles and pores.…”
mentioning
confidence: 99%
“…The effect of the core–shell rubber nanoparticles on the tensile properties of the epoxy resin was notable, leading to a reduction of 10–20% in the tensile strength and elastic modulus and an increase of 60–108% in the fracture toughness for the highest filler fraction. No considerable distinction in the fracture toughness among the additives was detected, thereby proving that the small (100 nm) and large (300 nm) core–shell rubber nanoparticles were equally efficient [ 12 ]. The glass transition temperature of the epoxy was gradually improved by 10–20 °C with the increase of core–shell rubber nanoparticles for all of the additives, which could be attributed to the high crosslink density and toughening effect of rubber modifiers, thereby testifying to their dissolution in the continuous epoxy phase.…”
mentioning
confidence: 99%
See 1 more Smart Citation